Accelerated aging modulates the toxicological properties of the diazo tattoo pigment PO13 - Lise Aubry; Marianne Vitipon; Aurélie Hirschler; Hélène Diemer; Thierry Rabilloud; Christine Carapito; Thierry Douki (Scientific Reports)
Abstract Pigment particles used in tattooing may exert long terms effect by releasing diffusible degradation products. In the present work, aqueous suspensions of the organic orange diazo pigment PO13 were aged by exposure to simulated sunlight at 40 °C. The morphology and the surface charge of PO13 particles were barely modified upon aging, but primary particles were released by de-agglomeration. Soluble photoproducts were detected in the liquid fractions. One of this photoproduct (DCBP) was produced in large amount in suspension in isopropanol and purified. The toxicological profiles of aged suspensions, their soluble fractions and DCBP were then determined on the keratinocyte cell line HaCaT. Impact of suspensions of PO13 on viability was hardly affected by aging. In contrast, the soluble fractions were more toxic after photo-aging. Suspensions and filtrates induced neither release of reactive oxygen species nor formation of DNA strand breaks. The samples exhibited only limited effects on the proteome of HaCaT cells. Conversely, DCBP was cytotoxic and induced the production of ROS, but was not genotoxic. DCBP was found to activate CYP450 monooxygenases known to be involved in the metabolism of xenobiotics. Altogether, our results show that aging of PO13 leads to the release of toxic soluble compounds.